Highly tough and conformal silk-based adhesive patches for sutureless repair of gastrointestinal and peripheral nerve defects - Min Zheng; Li-Zhiwei Du; Jie Zheng; Jingjing Tao; Yujun Wu; Lingyu Qiu; Shumeng Bai; Huanghao Yang (Bioactive Materials)
The use of tissue adhesive patches provides a promising therapeutic approach for sutureless repair of soft tissue injuries. However, existing tissue adhesive patches are confronted with serious challenges for clinical applications in the soft tissue environments with biological fluids and dynamic movements. Either their mechanical toughness does not match that of soft tissues, or they fail to establish effective interfacial bonding with tissues in wet conditions. The imbalance between the mechanical cohesion and interfacial adhesion of existing tissue adhesive patches severely restricts their conformal integration with wet surfaces of soft tissues in dynamic biological environments, leading to adhesion failure in clinical applications. Here, this study reports the design, fabrication, and preclinical therapeutic performance of a dual-layer silk-based adhesive patch (named SF patch) that quickly and conformally adheres to various soft tissues regardless of surrounding biological environments. The intimate microscopic structural connection between the highly tough hydrogel matrix layer and thin bioadhesive layer contributes to high mechanical cohesion and robust interfacial adhesion properties of the SF patch, thereby enabling sufficient integration with wet surfaces of soft tissues to withstand the interference of dynamic tissue movements. Ex vivo porcine and in vivo rat models validate its therapeutic efficacy for sutureless sealing and repair of gastrointestinal defects and peripheral nerve injuries. This SF patch is potentially valuable for clinical applications towards internal soft-tissue repair and functional reconstruction.